Radec Learning and Literacy: Enhancing Students’ Literacy through the Development of Radec Learning Model at Madrasah - Muhiddinur Kamal; Shafra; Elfiani; Abdulramae Sulonglfiani; Melyann Melani; Nofri Andy. N (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Literacy is one of the important things to be cultivated from an early age, because with literacy the window of the world will open. This research was an effort to foster literacy from an early age through the development of the Radec Learning model at Madrasah Ibtidaiyah. The purpose of this research was to produce a product in the form of developing a learning model using the Radec Learning model. The method used was Research and Development (RnD) to produce certain products and test the effectiveness of these products by adapting the McKenny Model as a stage consisting of preliminary research, prototyping phase, and assessment stage. The results of this study included: 1) The development of the Radec Learning model was significantly proven to be able to develop students’ learning outcomes at MIN 1 Pasaman; 2) This Radec Learning model was declared valid after being validated by the validator; and 3) There was a practical level of practical application of the Radec Learning model, with evidence of its development and increasing student creativity in learning. Thus, the application of the Radec Learning model of learning could develop literacy from an early age and as an alternative in the selection of learning models that would be applied in Madrasah Ibtidaiyah. Keywords: Radec Learning Model, Radec Learning, Students Literacy